Public administration and the protection of private rights : questioning its recognition and application under Ukrainian law - Brusakova, O. V.; Брусакова, О. В.; Karmaza, O.; Кармаза, О.; Vasylenko, V. M.; Василенко, В. М.; Moroz, V.; Мороз, В.; Viktor Vasylenko; Оксана Брусакова (Ius Humani. - 2022. - Vol. 11 (1). – P. 29-41, 2022)
Проаналізовано міжнародний досвід захисту приватних прав у сфері державного управління. Запропоновано конкретні шляхи імплементації зазначеного міжнародного досвіду у вітчизняну державу та її правову систему. З’ясовано сутність та характерні ознаки правових способів захисту законних інтересів приватних осіб у публічно-правових відносинах. Проаналізовано генезис розвитку способів захисту приватних прав у сфері державного управління. Особливу увагу звернуто на недостатню спроможність України щодо забезпечення недоторканності приватних прав, свобод та інтересів суб’єктів публічних правовідносин порівняно з розвиненими країнами Західної Європи та Північної Америки. Наголошено на поступовому підвищенні рівня демократії та верховенства права в Україні протягом останніх 20 років. Стверджується, що особливе «прискорення» зазначених реформ відбулося відразу після двох суспільно важливих подій, а саме Помаранчевої революції 2004 року та Революції Гідності 2013-2014 років. Проте так званий «енергетичний запал», набутий на початку реформи, в Україні гальмується.

Every society needs the recognition and protection of the rights of its citizens, and this becomes more proper for every administration in respecting this protection for the common good of its society. In this article, international experience of protecting private rights in the sphere of public administration has been analyzed. On the basis of the researched information the authors have provided concrete ways of implementing the specified international experience into domestic state and his legal system. The essence and characteristic features of legal ways to protect the legitimate interests of private individuals within public relations have been clarified among other things. The genesis of the development of the ways to protect private rights in the sphere of public administration has been analyzed. Particular attention has been paid to the insufficient capacity of Ukraine to ensure the inviolability of private rights, freedoms and interests of the entities of public legal relations, compared to the developed countries of Western Europe and North America. At the same time, the emphasis has been made on the gradual increase in the level of democracy and the rule of law in Ukraine over the last 20 years. It has been claimed that a special “acceleration” of the indicated reforms took place immediately after two socially important events, namely the Orange Revolution of 2004 and the Revolution of Dignity of 2013-2014. However, the so-called “energy fervor” gained at the beginning of the reform is slowing down in Ukraine.

Проанализирован международный опыт защиты частных прав в сфере государственного управления. Предложены конкретные пути имплементации указанного международного опыта в отечественное государство и его правовую систему. Выяснены сущность и характерные признаки правовых способов защиты законных интересов частных лиц в публично-правовых отношениях. Проанализирован генезис развития способов защиты частных прав в сфере государственного управления. Особое внимание уделено недостаточной способности Украины по обеспечению неприкосновенности частных прав, свобод и интересов субъектов публичных правоотношений по сравнению с развитыми странами Западной Европы и Северной Америки. Отмечено постепенное повышение уровня демократии и верховенства права в Украине в течение последних 20 лет.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зарубіжний досвід; foreign experience; зарубежный опыт; законодавство; legislation; законодательство; державне управління; государственное управление; захист прав; protection of rights; защита прав; приватна особа; private individual; частное лицо; державна політика; state policy; государственная политика; public administration; непорушність прав; inviolability of rights; захист приватних прав; protection of private rights; защита частных прав; publikatsii u zarubizhnomu vydanni